Urinary tract infections in patients with decompensated liver cirrhosis, listed for liver transplantation - P. D. Bessonov; I. V. Borzunov; E. N. Bessonova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To study the urinary infection rate in patients with liver cirrhosis (LC) and indications for liver transplantation with assessment of etiologic spectrum and features of the progression of liver disease at development of this complication. Material and methods. The study included patients with liver cirrhosis Child Pugh class B and C with indications for liver transplantation, who were hospitalized at Sverdlovsk Regional hepatological center for liver disease decompensation in 2015 (n=137). Results. Of all enrolled patients 28,5% had urinary infectious complications. In those with more severe liver decompensation (Child-Pugh class C), the rate of patients with urinary tract infection was higher (66,7%). The most commen signs included leukocyturia and bacteriuria. Esсheriсhia сoli и Klebsiella pneumoniae were the most common infectious agents in liver cirrhosis patients. Frequency of urinary tract infections was higher in those with severe liver cirrhosis complications (in past history as well) such as hepatic encephalopathy, ascites, spontaneous bacterial peritonitis. Conclusion. High frequency of infections at decompensated liver cirrhosis require thorough examination of these patients using all available diagnostic methods. Early diagnostics and treatment of urinary tract infections is of paramount importance for patients, listed for liver transplantation, for it can help to keep the patient in waiting list and improve the operation outcomes.